The prevalence and risk factors of burnout and its association with mental issues and quality of life among hungarian postal workers: a cross-sectional study - Miklós Kovács; György Muity; Ádám Szapáry; Zsolt Nemeskéri; Imre Váradi; Krisztián Kapus; Antal Tibold; Nikoletta Magyar Zalayné; Lilla Horvath; Gergely Fehér (BMC, 2023)
Abstract Background Burnout is one of the most extensively studied phenomena of the twenty-first century; which has been extensively studied among helping professions, although it can be broadened to several other types of occupation. Based on our knowledge and literature search, no similar studies have been carried out among postal workes to date. Methods This cross-sectional questionnaire-based epidemiological study was carried out between May 2021 and January 2022 in five counties in Hungary with the recruitment of postal delivery workers focusing on (1) the prevalence of burnout among postal delivery workers; (2) including the role of demographic parameters, duration of employment as well as the presence of secondary employment; (3) and also analyzed the role of several risk factors and medical conditions; (4) and we also examined the possible association between depression, insomnia and quality of life and burnout. Results Overall 1300 questionnaires were successfully delivered and 1034 responses received (response rate of 79.5%). Three hundred sixty-eight males (35.6%) and six hundred sixty-six females (64.4%) participated in our study. The prevalence of burnout was 50.8% (525/1034) in this study population (mean score 2.74 ± 0.33). Logistic regression analysis showed that female gender [OR = 2.380, 95% CI: 1.731 to 2.554], first workplace [OR = 1.891, 95% CI: 1.582 to 2.162] and working more than 30 years [OR = 1.901, 95% CI: 1.608 to 2.326] have significantly increased the likelyhood of burnout as well as the history of muscoskeletal pain [OR = 1.156, 95% CI: 1.009 to1.342], current quality of life [OR = 1.602, 95% CI: 1.473 to 1.669] and the presence of sleep disturbance [OR = 1.289, 95% CI: 1.066 to 1.716]. Conclusion This is the first study in Hungary to investigate the prevalence of burnout among postal workers and to explore the relationship between burnout and mental health problems. Our study underlines the clinical importance of burnout and draws attention to the need for appropriate prevention and treatment strategies.